Efficacy of Intra-articular injections of Platelet Rich Plasma (PRP) in Osteoarthritis Knee. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the effectiveness of intra-articular injections of Platelet Rich Plasma (PRP) in early Osteoarthritis knee in terms of pain reduction and improvements in functional outcome.Methods: This descriptive study was conducted in Department of Orthopedics Surgery Punjab Rangers Teaching Hospital Lahore/ Rahbar Medical and Dental College Lahore from 23rd March 2018 to 23rd March 2021.All patients with early osteoarthritis knee fulfilling the inclusion criteria were administered two intra-articular pure PRP injections. Follow up assessment was done at 6 weeks, 3 months, 6 months and one year for pain reduction measured on Visual Analog Scale (VAS) and functional improvement assessed with Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. The pre and post injection WOMAC and VAS values were compared P value calculated with  Student-t test. P value